2022
DOI: 10.1177/00207640221104698
|View full text |Cite
|
Sign up to set email alerts
|

Burnout syndrome (BOS) among resident doctors in an Egyptian tertiary care university hospital: Prevalence and determinants during the COVID-19 pandemic

Abstract: Objectives: The current study aimed to detect the BOS prevalence and determinants among residents working during the second wave of the COVID-19 pandemic in an Egyptian tertiary university referral hospital. Methods: A cross-sectional study evaluating the working period from June to November 2020 during the COVID-19 pandemic second wave, through a five sections questionnaire evaluating: 1 − sociodemographic characteristics, 2 − job characteristics, 3 − negative thoughts related to their job, 4 − resident’s hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Burnout is a work-related syndrome of emotional exhaustion (EE), depersonalization (DP) and a reduced perception of personal accomplishment (PA) [ 5 ]. Multiple studies have indicated that during the COVID‐19 pandemic, nurses [ 6 ], physicians [ 7 ], surgeons [ 8 ], residents [ 9 ] and medical students all experience high levels of burnout [ 10 ]. Significant differences were noticed across various specialities [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Burnout is a work-related syndrome of emotional exhaustion (EE), depersonalization (DP) and a reduced perception of personal accomplishment (PA) [ 5 ]. Multiple studies have indicated that during the COVID‐19 pandemic, nurses [ 6 ], physicians [ 7 ], surgeons [ 8 ], residents [ 9 ] and medical students all experience high levels of burnout [ 10 ]. Significant differences were noticed across various specialities [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported in Italy 37%, Spain 41%, Portuguese 53% and Australia as 30%. 13 Studies in Egypt mentioned that one in two doctors had high EE and DP and low PA. 14 Burnout syndrome has detrimental effects on the efficiency of doctors. 9 The doctors at early stage of their careers have increased workload, more workplace responsibilities, sleep deprivation and low income.…”
Section: Introductionmentioning
confidence: 99%